2022
DOI: 10.1007/s11270-022-05760-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Variations in the Presence of Giardia and Cryptosporidium in Rural Drinking Water Supply Systems in Different Municipalities of Antioquia, Colombia

Abstract: This study evaluated the seasonal and spatial variations in the presence of Giardia and Cryptosporidium in rural drinking water supply systems of different municipalities of Antioquia. The municipalities evaluated were Envigado, Caldas, Sabaneta, La Estrella, Itagüi, Bello, Barbosa, Copacabana, and Girardota, located in the department of Antioquia, Colombia. The experimentation was carried out over 9 sampling campaigns in the period between July 2019 and November 2020. This period encompassed the two seasons p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the present study, no significant seasonal variations were observed for Giardia and Cryptosporidium in the surface water. A previous study conducted in Colombia (Escobar et al 2022 ) also reported that seasonality did not have a strong impact on the occurrence of Cryptosporidium and Giardia in drinking water systems. In contrast, a study conducted in Egypt (Hamdy et al 2019 ) found evidence of seasonality in the prevalence of both Giardia and Cryptosporidium cysts in tap water, with higher levels observed during the summer season.…”
Section: Discussionmentioning
confidence: 83%
“…In the present study, no significant seasonal variations were observed for Giardia and Cryptosporidium in the surface water. A previous study conducted in Colombia (Escobar et al 2022 ) also reported that seasonality did not have a strong impact on the occurrence of Cryptosporidium and Giardia in drinking water systems. In contrast, a study conducted in Egypt (Hamdy et al 2019 ) found evidence of seasonality in the prevalence of both Giardia and Cryptosporidium cysts in tap water, with higher levels observed during the summer season.…”
Section: Discussionmentioning
confidence: 83%
“…Water To calculate the IRCA, not all 22 parameters must be present. Consequently, 11 parameters were used in this investigation [12,13] .To determine the IRCA, Utilizing Equation 6,…”
Section: Water Quality Index (Waqwi) Weighted Arithmetic Methodsmentioning
confidence: 99%
“…(13) 2.2.6. Iraq's Index of Water Quality (Iraqi WQI) these four procedures were used to create the Iraqi WQI.…”
mentioning
confidence: 99%
“…The risk of contamination is significantly higher in surface waters when compared to underground waters, because of the spilling of treated and untreated domestic sewage (Bonatti et al, 2023;Cheng et al, 2009;Toledo; Martins; Freire, 2017) and the superficial water outflow containing bovine faeces (Escobar et al, 2022;Imre et al, 2017).…”
Section: Introductionmentioning
confidence: 99%